EFEKTIVITAS PELAKSANAAN PSBB DALAM RANGKA PENGENDALIAN COVID-19 DI KOTA PEKANBARU - Siti Asha Amara; Zailli Rusli (Cross-border, 2022)
Pembatasan Sosial Berskala Besar (PSBB) are a form of policy made by the Government in the context of controlling Covid-19. The Pembatasan Sosial Berskala Besar (PSBB) to overcome Covid-19 is based on Decree No. 21 of 2020 concerning Large-Scale Social Restrictions related to the acceleration of handling Covid-19 infections, the PSBB policy is an official policy taken by the government which is implemented in Indonesia based on permits and Minister of Health in the context of dealing with Covid-19. The purpose of this study was to determine the effectiveness of implementing Pembatasan Sosial Berskala Besar (PSBB) in the context of controlling COVID-19 in Pekanbaru City and to describe the obstacles in implementing PSBB in Pekanbaru City. The research method used is descriptive qualitative research, with interview and documentation data collection techniques. The results of this study indicate that the effectiveness of the PSBB implementation in the context of controlling covid-19 in Pekanbaru City can be seen from four indicators, namely Accuracy of Targets, Program Socialization, Program Targets, Program Monitoring which has not been effective because there are still people who do not comply with regulations due to various factors.